1997
DOI: 10.1111/j.1525-1314.1997.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of discordant U‐Pb zircon ages: An evaluation

Abstract: A B S TR A CT The most widely used technique for the determination of high precision mineral growth ages in igneous and metamorphic rocks is dating of zircons with the U-Pb method. The interpretation of these ages, particularly in metamorphic settings, is hampered by an incomplete understanding of the common phenomenon of partial Pb-loss in zircon. In principle, this Pb-loss may occur in four very different ways: diffusion in metamict zircon, diffusion in pristine zircon, leaching from metamict zircon and recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
201
1
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 525 publications
(213 citation statements)
references
References 75 publications
9
201
1
2
Order By: Relevance
“…Interpretation of zircon U Pb data in metamorphic rocks is often complex (see review in Mezger and Krogstad 1997). In the present study, we dated zircons from a leucosome in order to constrain its crystallisation age and zircons from an eclogite-facies paragneiss (GCH-99-1) and from a granulite-facies paragneiss .…”
Section: Zircon Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Interpretation of zircon U Pb data in metamorphic rocks is often complex (see review in Mezger and Krogstad 1997). In the present study, we dated zircons from a leucosome in order to constrain its crystallisation age and zircons from an eclogite-facies paragneiss (GCH-99-1) and from a granulite-facies paragneiss .…”
Section: Zircon Datamentioning
confidence: 99%
“…In this case we consider that the lower intercept is meaningful (cf. Discussion in Mezger and Krogstad 1997) and represents an event at ca. 470 480 Ma or slightly older.…”
Section: Zircon Datamentioning
confidence: 99%
“…A number of studies have found that zircon chemical and isotopic signatures can be altered by various mechanisms: Pb can be locally lost (e.g. Mezger and Krogstad 1997;Geisler et al 2002;McFarlane et al 2005) or gained (e.g. McFarlane et al 2005), or Pb can be redistributed at sub-micron scale (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is relevant for discussions of the geological relevance of zircon age data from high-grade metamorphic zircon. The U-Pb stability of the low U-Th relatively crystalline zircons is in accord with the very low diffusivities of U, Th and Pb (Cherniak et al 1997;Lee et al 1997) and the very high closure temperatures for Pb loss in zircon (Lee et al 1997), indicating that volume diffusion in intact zircon crystals is not the dominant process of Pb loss (Mezger and Krogstad 1997).…”
Section: Implications To Zirconologymentioning
confidence: 60%